Study of Proportions of Porang Slurry and Coconut Milk and the Addition of Podang Mango Fruit on the Physicochemical And Organoleptic Characteristics of Plant Based Ice Cream - Briliansyah, Resi; Winarti, Sri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This research aims to determine the effect of the substitution of coconut milk and porang tuber porridge and the addition of podang mango on the physicochemical and organoleptic quality of vegetable ice cream. The research used a Completely Randomized Design (CRD) with two factors and two replications. Data analysis using ANOVA was continued with the Duncan multiple range test (DMRT) at a confidence level of 5%. The first factor is the substitution of porang tuber slurry for coconut milk (10:90 (A1), 20:80 (A2), 30:70 (A3)). The second factor is the concentration of podang mango (15% (B1), 20% (B2), 25% (B3)). Parameters observed include protein content, overrun, melting speed, color analysis, total dissolved solids, viscosity, fat content, dietary fiber, vitamin C, and organoleptic analysis including texture, aroma, color, and taste. The results of the treatment of porang tuber slurry substitution for coconut milk and the concentration of porang mango had a significant effect on protein content, total solids, overrun, melting time, and viscosity. The best treatment in this study was vegetable ice cream with the substitution of porang tuber slurry for coconut milk (30:70%) and the addition of podang mango (15%) with a protein content of 4.09%, fat content of 3.99%, the dietary fiber content of 4.38%, vitamin C of 26.27%, melting time 18.46 minutes, overrun of 23.09%, viscosity of 1685%, total solids of 38.07%, lightness of 64.60, redness of 47.70, yellowness of 79.21, and average hedonic value of color of 4.0, aroma of 3.67, taste 3.4, and texture of 3.7.